UPAYA PEMERINTAH UNTUK MENCAPAI NATIONALLY DETERMINED CONTRIBUTION DALAM KERANGKA KEBIJAKAN KARBON BIRU INDONESIA - Fatimah Gyn (Faculty of Law Universitas Sebelas Maret, 2024)
Currently, Indonesia has not yet included the blue carbon component in its Nationally Determined Contribution (NDC). Therefore, this research aims to determine whether the current policy framework of the Indonesian government is oriented towards incorporating blue carbon to achieve the NDC. This study is a doctrinal, descriptive research. The sources of legal materials used are primary and secondary legal materials, collected through literature review as the data collection technique. Meanwhile, the legal material analysis technique employed is the syllogism method with deductive reasoning, based on all international and national legal regulations. The results of this research show that current policies regarding blue carbon in Indonesia are still limited to general regulations under the Indonesian Maritime Policy. The absence of specific regulations on blue carbon in Indonesia means that the existing policies are not yet oriented towards reducing greenhouse gas (GHG) emissions. In order to achieve Indonesia's NDC and reduce GHG emissions by 26% independently and 41% with international assistance, while there is a significant potential for blue carbon in Indonesia to contribute to the GHG reduction target, the lack of specific policies regulating blue carbon has resulted in its underutilization.